Dragana Božić Lenard - Chmelíková, Gabriela (Scripta manent (Ljubljana), 2025)
o address the rapid development of computer science, the reviewed coursebook provides a pro-fessional insight into the required knowledge and skills in this field/area. The coursebook English for Computer Science – Part I, the first part of the planned trilogy, complemented by Power Up Zone – Part I, an interactive and supplementary section, was designed to equip university students with the lan-guage skills and technical vocabulary needed to master their field of study, specifically in the context of English for Specific Academic Purposes (ESAP), English for Specific Purposes (ESP), and General English (GE), aiming to blend English language learning with practical, industry-relevant content, fos-tering both linguistic proficiency as well as technical competence. The coursebook, with its regularly updateable handouts and accessible materials in the virtual learning environment, (VLE) ensures that students stay informed of current developments in the world of computer science.
Keywords: angleščina kot tuji jezik stroke; computer science; ESP; izobraževanje učiteljev; professors; računalništvo; recenzija; textbook; učbenik